Scientific Approach-Based Student Worksheets on Light and Its Properties to Enhance Learning Outcomes of Fifth Grade Elementary Students - Sitepu, Shella Febina Br; Suranata, Kadek; Yudiana, Kadek (Universitas Pendidikan Ganesha, 2024)
The lack of instructional media that stimulate students' critical thinking skills has resulted in low learning outcomes. This study aims to analyze the effectiveness of scientific approach-based student worksheets (LKPD) on the topic of light and its properties in improving the learning outcomes of fifth-grade elementary students. This research employed a development design using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of the study were 14 fifth-grade students. Data collection methods included observation, interviews, and questionnaires, with instruments such as questionnaire sheets and multiple-choice tests. Data analysis techniques involved qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical analysis using the t-test. The findings revealed that the effectiveness test of the scientific approach-based LKPD yielded a significant result (2-tailed) of 0.000, indicating that H0 was rejected and H1 was accepted. This concludes that there is a significant difference in learning outcomes before and after using the scientific approach-based LKPD, particularly on the topic of light and its properties. The innovation of LKPD with a scientific approach to the material of light and its properties has implications as an example for teachers in implementing learning based on a scientific approach in elementary schools.